Membangun Kesadaran Kebersihan Diri dan Lingkungan Pada Siswa TK & SD Tunas Benih Kasih Surabaya - Prida Ariani Ambar Astuti; Prayogo Maulana; Agathon Agnar Ramadhan; Danny Alfaridzi; Grace Putri Amelia; Rahman Hakim Averus (Prapanca : Jurnal Abdimas, 2021)
The government continues to strive to educate the public to care about environmental cleanliness. Even so, cases of disease caused by a lack of awareness of environmental hygiene have increased every year. For this reason, awareness of environmental cleanliness needs to be instilled from an early age so that disease cases caused by hygiene problems can be overcome. Preliminary research has identified that there are still many kindergarten and elementary school students in Tunas Benih Kasih Surabaya who are accustomed to littering. Most students are ignorant of the cleanliness of the classroom and school environment by throwing food wrappers and paper carelessly. The findings of this preliminary research then become the basis for the use of educational posters and videos as a tool to build awareness of personal and environmental hygiene in Tunas Benih Kasih Surabaya kindergarten and elementary school students. Educational activities to improve health have been shown to be able to change people's behavior. Determining the theme, formulating messages, choosing words and photos to be used, and combining other elements to make interesting posters and videos, are important stages in making educational videos and posters. In the future, this community service activity can be continued by conducting research using experimental methods to determine the impact of these educational videos and posters on the awareness of kindergarten and elementary school students of Tunas Benih Kasih Surabaya in maintaining personal hygiene and the environment.